Comparison of breeder/layer coccidiosis vaccines: Part 2: Onset of immunity – attenuated vaccines. (20th September 2017) - Mathis, Greg F; Newman, Linnea J; Fitz-Coy, Steve; Lumpkins, Brett; Charette, Robert
Abstract: Coccidiosis control for breeding and laying chickens requires the development of immunity against multiple Eimeria species. Only one vaccine was widely available to producers in the European Union (EU) from 1991 until 2015. Recently, 2 new products have been introduced to the market. The 3 vaccines were compared with respect to the onset of immunity in pen studies, where sample birds were challenged at 21, 25, 28, and 32 d of age to determine the time at which lesion scores became significantly different from unvaccinated controls, the "onset of immunity." The vaccines were given by oral gavage to eliminate any effect of application methodology on the onset of immunity. "Complete Immunity, " defined as no coccidiosis lesions following challenge, was only achieved for one species ( Eimeria tenella ) by one vaccine through the final challenge at 32 d. Immunity remained incomplete for all other challenge groups for the duration of the experiment. Onset of immunity was detected by 25 d of age in only one vaccine group for all 5 challenge species tested ( E. acervulina, E. maxima, E. tenella, E. necatrix, E. brunetti ); and while onset of immunity was detected for some species with the other vaccines by 21 to 32 d of age, neither of the other 2 vaccines demonstrated onset of immunity to all 5 challenge species by the end of the experiment. Delayed onset of immunity could adversely affect pullet weight with early field challenge, as indicated by bird weights taken before and after challenge.